Some isometrical identities in the wave equation - Saburou Saitoh (International Journal of Mathematics and Mathematical Sciences)
We consider the usual wave equation utt(x,t)=c2uxx(x,t) on the real line with some typical initial and boundary conditions. In each case, we establish a natural isometrical identity and inverse formula between the sourse function and the response function.